Structure of the Open Reading Frame 49 Protein Encoded by Kaposi Sarcoma-Associated Herpesvirus - Hew, Kelly (2017)
Herpesviruses alternate between the latent and the lytic life cycle. Switching into the lytic life cycle is important for herpesviral replication and disease pathogenesis. Activation of a transcription factor replication and transcription activator (RTA) has been demonstrated to govern this switch in Kaposi's sarcoma-associated herpesvirus (KSHV). The protein encoded by open reading frame 49 from KSHV (ORF49KSHV) has been shown to upregulate lytic replication in KSHV by enhancing the activities of the RTA. We have solved the crystal structure of the ORF49KSHV protein to a resolution of 2.4 Å. The ORF49KSHV protein has a novel fold consisting of 12 alpha-helices bundled into two pseudodomains. Most notably are distinct charged patches on the protein surface, which are possible protein-protein interaction sites. Homologs of the ORF49KSHV protein in the gammaherpesvirus subfamily have low sequence similarities. Conserved residues are mainly located in the hydrophobic regions, suggesting that they are more likely to play important structural roles than functional ones. Based on the identification and position of three sulfates binding to the positive areas, we performed some initial protein-DNA binding studies by analyzing the thermal stabilization of the protein in the presence of DNA. The ORF49KSHV protein is stabilized in a dose-responsive manner by double-stranded oligonucleotides, suggesting actual DNA interaction and binding. Biolayer interferometry studies also demonstrated that the ORF49KSHV protein binds these oligonucleotides.